Relevance of necroptosis in the hearts subjected to acute versus chronic ischemia/reperfusion injury. (10th June 2022) - Horvath, C; Szobi, A; Young, M; Jarabicova, I; Hrdlicka, J; Neckar, J; Lewis, M; Kolar, F; Ravingerova, T; Suleiman, MS; Adameova, A
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Slovak Research and Development Agency Medical Research Council Grant Necroptosis, a necrosis-like programmed cell death modality dependent on the activity of receptor-interacting protein kinase 3 (RIP3) and mixed lineage domain kinase domain-like pseudokinase (MLKL), plays a prominent role in mediating myocardial ischemia/reperfusion injury. However, the extent to which necroptosis contributes to such damage under short and long reperfusion has not been evaluated in detail. In Wistar rat hearts, subjected to global 30-min ischemia followed by an acute 10-min reperfusion period, with compromised cardiac function, no changes in the protein expression of the main necroptotic markers (pThr231/Ser232-RIP3, MLKL) were found. Likewise, the non-canonical pathways of necroptosis involving Ca2+/calmodulin dependent protein kinase II–mitochondrial permeability transition pore (CaMKII–mPTP) or phosphoglycerate mutase 5–dynamin-related protein 1 (PGAM5–Drp1) axes were unlikely affected by such short reperfusion. In contrast, hearts subjected to global 30-min ischemia followed by a prolonged 40-min reperfusion period exhibited worsened hemodynamic parameters what was accompanied by the increased levels of RIP3, pSer229-RIP3 and MLKL. Moreover, this reperfusion period induced MLKL translocation to the plasma membrane, indicating necroptosis execution with resultant very likely cell disruption. Similarly, activated necroptosis, evidenced by the higher levels of proteins of the canonical pathway, has been suggested to contribute to the pathogenesis of post-infarction heart failure (30-min ischemia, 42-day reperfusion). Collectively, these findings suggest that short reperfusion seems to be insufficient to induce necroptosis in the heart and the molecular mechanisms being activated during the longer reperfusion phase are needed to promote necroptotic cell dying. Therefore, inhibition of necroptosis might represent a cardioprotective strategy in the settings of chronic, but not acute myocardial ischemia/reperfusion injury.